Primary gastric tuberculosis presenting as gastric outlet obstruction: a case report and review of the literature - Arabi, Nassir Alhaboob (J Med Case Rep, 2015)
INTRODUCTION: Tuberculosis is a major health problem worldwide. Sudan has high burden of tuberculosis (TB) with a prevalence of 209 cases per 100,000 of the population and it is commonly presented with pulmonary disease but involvement of the gastrointestinal tract is not uncommon. Abdominal tuberculosis comprises about 1–3 % of all cases of tuberculosis and about 12% of extrapulmonary tuberculosis. It involves the ileocecal region, but involvement of stomach and duodenum are rare sites. Here we present an unusual case of gastric outlet obstruction due to gastric tuberculosis. CASE PRESENTATION: A 54-year-old Sudanese man presented with a non-bile stain persistent projectile vomiting, and epigastric pain for two years associated with marked loss of weight. There is no fever or cough. He was on antacid, physical examination showed BMI 18 and stable vital signs. He was not pale or jaundiced, there was no cervical lymphadenopathy and chest was clear. Abdominal examination was normal apart of positive succussion splash. The results of haematological tests were normal, ESR was 30 mm/hr, hepatitis B, C and HIV were negative. Upper gastrointestinal endoscopy showed that the stomach was full of fluid and food particles and ulcerated mass in the pylorus extended to the proximal part of the duodenum with severe narrowing of the pylorus. The lesion biopsied and the result revealed active inflammatory cells, cryptitis and multiple lymphoid follicles, no malignancy seen. Sonographic test showed hypodense pyloric mass, enlarged para-aortic and mesenteric lymph nodes and mild pelvic ascites. A computed tomography scan of the abdomen and pelvis showed antral hypodense lesions multiple mesenteric lymphadenopathies peritoneal thickening and ascites. Chest X-ray was normal. Intra-operative findings were dilated stomach and pylorus mass with multiple mesenteric lymph nodes, peritoneal and omental seedlings all over with small nodules on the surface of the liver, gastro-jejunostomy was done. Histopathology confirmed the diagnosis of abdominal tuberculosis. Postoperative event was uneventful. Patient received anti-tuberculous. CONCLUSIONS: Here we presented an unusual case of gastric outlet obstruction due to primary gastric tuberculosis, patient underwent surgery to relief his symptoms and received anti-tuberculous.